Appraisal the potential of central iran, in the context of health tourism. - Ladan Rokni; Ahmad Pourahmad; Mohammad Hassan Moteiey Langroudi; Mehdi Rezaeiy Mahmoudi; Najmeh Heidarzadeh (Tehran University of Medical Sciences, 2013)
The aim of the present study was to appraisal the prose and cone of Shiraz City in terms of its potential in the context of health tourism.The statistical sample included medical and health tourism sector in the city of Shiraz in the northwest of Fars Province, south of Iran. The efficient authorities on the topic were identified through the hospitals engaging in medical tourism. The research was based on theoretical sampling through which the experienced people of extensive knowledge on medical tourism were interviewed.Active hospitals on attraction foreign patients averagely admit 15 and 50 foreign patients monthly and annually, respectively. Arab countries in the Persian Gulf were detected as the main marketing for Shiraz medical tourism. Oman encompassed the highest rate with 20% of admitted patients. Eye treatments with 30% and orthopedic with 6% were demonstrated as the highest and lowest rates in terms of foreign patients' needs, respectively. Closeness of cultural and religious beliefs and familial relationships on one hand and trusting to Iranian physicians on the other hand were amongst the most reasons for selecting Iran as a destination for medical tourism by patients.Implementing 4 strategies on monitoring medical tourism would result into significant improvement of attracting more foreigner patients not only into Shiraz but all around Iran. These items have been discussed in the text.